Outcome after surgical repair of sealed rupture abdominal aortic aneurysms: a case-control study - Bonamigo, Telmo Pedro (2006)
OBJECTIVE: To establish, in a case-control study, the early mortality and long-term survival after surgical correction of sealed rupture abdominal aortic aneurysm, compared to controls who underwent standard, nonruptured abdominal aortic aneurysm repair. PATIENTS AND METHODS: From January 1992 to December 2002, 465 patients underwent infrarenal abdominal aortic aneurysm repair. Of those, 13 had sealed rupture abdominal aortic aneurysm (2.8%). These cases were compared to 26 controlsin which surgical repair was performed immediately preceding or succeeding each one of the sealed rupture abdominal aortic aneurysm surgeries. RESULTS: Age, sex, risk factors for atherosclerosis, associated disease, and cardiac ischemia were similar between groups. Patients with sealed rupture abdominal aortic aneurysm presented a higher incidence of lumbar pain than controls (92.3% versus 3.9%; P < .001); fever and weight loss were detected in 5 (38.5%) patients with SAAA and in none of controls (P = .0022). Mean red blood cell transfusion was greater for sealed rupture abdominal aortic aneurysm than controls (1,516 ± 697 vs. 773 ± 463 mL (P = .0003). Postoperative complications were similar between groups. Early mortality was 7.7% for sealed rupture abdominal aortic aneurysm and 0% for controls. Five-year survival was significantly lower for sealed rupture abdominal aortic aneurysm (68.4%) than for controls (84.4%, P = .04). CONCLUSION: We conclude that sealed rupture abdominal aortic aneurysm presents diagnostic and surgical challenges that can be adequately managed, achieving early postoperative mortality and complication rates that are similar to standard abdominal aortic aneurysm. However, patients with sealed rupture abdominal aortic aneurysm present higher mortality in the long term compared with patients having standard abdominal aortic aneurysm.